À la recherche de la femme idéale… Les stéréotypes de genre et de race dans le commerce de « promises par correspondance » - Gwenola Ricordeau (Genre, Sexualité et Société)
This essay deals with erotic fantasies in the advertising materials of the mail-order bride industry, which are distributed mainly on the Internet. These international introduction agencies target Western men eager to marry women categorized as “Asian“, “Slavic” or “African”. Advertising materials contain many prejudices towards Western women. The “submission” and “family values” of “exotic” women are underlined. International introduction agencies often advertise the sensuality or even the “exotic sexuality” of “Asian”, “Slavic” or “African” women. The erotic fantasies to which “Asia”, “Russia” and “Africa” play host show how gender and race stereotypes are variously interlocked.